Environmental perspectives of energy scenario in Malaysia. - Abas, Fuad (1990)
The paper presents the planning for energy production in order to cater for the need of economic development until the turn of the century. The national four fuel strategy and domestic gas utilisation policy formed the backbone of the long term planning. Economic factors, national security and environmental considerations play important roles in determining the course of action. A survey of several energy generation projects and their environmental aspects are described. The environmental impacts of energy utilisation is analysed. The present regulatory measures are surveved. Through comparison, price indication of 'cleaning' technology is made. The paper concludes by emphasising the need to have a indigenous approach to energy planning and that national and regional considerations must dominate.